Household air pollution and arthritis in low-and middle-income countries: Cross-sectional evidence from the World Health Organization's study on Global Ageing and Adult Health. - Shelby S Yamamoto; Elaine Yacyshyn; Gian S Jhangri; Arvind Chopra; Divya Parmar; C Allyson Jones (PLoS ONE)
Background Evidence points to a clear link between air pollution exposure and several chronic diseases though investigations regarding arthritis are still lacking. Emerging evidence suggests an association between ambient air pollution and rheumatoid arthritis. Household air pollution exposure, conversely, is largely unstudied but may be an important consideration for arthritis, particularly in low- and middle-income countries (LMICs), where cooking and heating activities can generate high indoor air pollutant levels. Methods We investigated the association of household air pollution (electricity vs. gas; kerosene/paraffin; coal/charcoal; wood; or agriculture/crop/animal dung/shrubs/grass as the main fuel used for cooking) and arthritis in six LMICs (China, Ghana, India, Mexico, the Russian Federation, South Africa) using data from Wave I of the World Health Organization Study on Global AGEing and Adult Health (SAGE) (2007-2010). Multivariable analyses were adjusted for sociodemographic, household and lifestyle characteristics and several comorbidities. Results The use of gas (aOR = 1.76, 95%CI: 1.40-2.21); coal (aOR = 1.74, 95%CI: 1.22-2.47); wood (aOR = 1.69, 95%CI: 1.30-2.19); or agriculture/crop/animal dung/shrubs/grass: aOR = 1.95 (1.46-2.61) fuels for cooking were strongly associated with an increased odds of arthritis, compared to electricity in cluster and stratified adjusted analyses. Gender (female), age (≥50 years), overweight (25.0 ≤BMI<30.0 kg/m2), obesity (BMI ≥30.0 kg/m2), former and current alcohol consumption, and the comorbidities angina pectoris, diabetes, chronic lung disease, depression and hypertension were also associated with a higher odds of arthritis. Underweight (BMI<18.5 kg/m2) and higher education levels (college/university completed/post-graduate studies) were associated with a lower odds of arthritis. Conclusions These findings suggest that exposure to household air pollution from cook fuels is associated with an increased odds of arthritis in these regions, which warrants further investigation.